2004
DOI: 10.4049/jimmunol.173.9.5721
|View full text |Cite
|
Sign up to set email alerts
|

A New Pharmacological Effect of Salicylates: Inhibition of NFAT-Dependent Transcription

Abstract: The anti-inflammatory effects of salicylates, originally attributed to inhibition of cyclooxygenase activity, are currently known to involve additional mechanisms. In this study we investigated the possible modulation by salicylates of NFAT-mediated transcription in lymphocytic and monocytic cell lines. RNase protection assays showed that 2-acetoxy-4-trifluoromethylbenzoic acid (triflusal) inhibited, in a dose-dependent manner, mRNA expression of several cytokine genes, most of which are NFAT-regulated and cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 41 publications
2
23
1
Order By: Relevance
“…Our results showed that MXF significantly inhibited the VP-16-enhanced production of IL-8, TNF-a and IL1b in THP-1 cells, but not in Jurkat cells. Accordingly, Aceves et al (2004) reported a different pattern of gene expression in THP-1 and Jurkat cells on their exposure to chemotherapeutic drugs. This may suggest that the inhibitory effect of MXF on the release of proinflammatory cytokines by cells is tumour cell specific.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that MXF significantly inhibited the VP-16-enhanced production of IL-8, TNF-a and IL1b in THP-1 cells, but not in Jurkat cells. Accordingly, Aceves et al (2004) reported a different pattern of gene expression in THP-1 and Jurkat cells on their exposure to chemotherapeutic drugs. This may suggest that the inhibitory effect of MXF on the release of proinflammatory cytokines by cells is tumour cell specific.…”
Section: Discussionmentioning
confidence: 99%
“…NF-AT may be regulated at different levels: phosphorylation/dephosphorylation, subcellular localization, DNA binding activity, and transactivation (Rao et al, 1997;Aceves et al, 2004). Among these possibilities, our data indicate that UR-1505 acts at the level of DNA binding and/or transactivation, because UR-1505 failed to inhibit NF-AT translocation into the nucleus in response to ionomycin stimulation of HeLa cells.…”
Section: Discussionmentioning
confidence: 64%
“…Our results are in agreement with previous data reporting that salicylates inhibit cell proliferation through inhibition of Ca 2ϩ /calcineurin/NFAT pathway (Nú ñ ez et al, 2006) because this pathway is activated after TCR engagement. On the other hand, Aceves et al (2004) have shown that salicylates prevent NF-AT-dependent gene expression. Therefore, NF-AT is a target for salicylates and inhibition of NF-AT results in decreased cell proliferation and cytokine production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the decay of b-actin and GADPH mRNA was also significant in actinomycin D-treated PMN (not shown). Further assessment of transcriptional regulation of COX-2 expression was carried out by looking at the effect of 2-hydroxy-4-trifluoromethylbenzoic acid, an inhibitor of both NF-jB and NF-AT [30,31], which is an useful tool to address in a single-step transcriptional regulation since both transcription factors have been involved in COX-2 regulation in different cell types [32,33]. As shown in Fig.…”
Section: Mechanisms Involved In Cox-2 Induction In Human Pmnmentioning
confidence: 99%